2005
DOI: 10.1057/palgrave.jors.2601842
|View full text |Cite
|
Sign up to set email alerts
|

Learning and forgetting-based worker selection for tasks of varying complexity

Abstract: This paper presents an approach for selecting workers for tasks of varying complexity based on individual learning and forgetting characteristics in order to improve system productivity. The performance of a learning and forgetting-based selection (LFBS) policy is examined using simulation and compared to a baseline policy representing criteria used in practice. The effects of factors including worker redundancy and task-tenure on productivity are also examined in the environment of continuously staffed indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…With MaxiMax O and MaxiMin O, workers are ranked based on knowledge of all four L/F parameters, and estimates the expected output from each task. With MaxiMax P and MaxiMin P, we rely solely on the single prior expertise parameter, p. We first note that, similar to results from Nembhard and Osothsilp (2005), these partially informed policies perform no worse than the baseline, and in some cases significantly outperform the baseline. Secondly, while Nembhard and Osothsilp suggest that basing worker selection and assignment on L/F characteristics can provide the opportunity for improvement, we further demonstrate that several straightforward policies, which do not require instance specific optimisation, can also provide such opportunities.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…With MaxiMax O and MaxiMin O, workers are ranked based on knowledge of all four L/F parameters, and estimates the expected output from each task. With MaxiMax P and MaxiMin P, we rely solely on the single prior expertise parameter, p. We first note that, similar to results from Nembhard and Osothsilp (2005), these partially informed policies perform no worse than the baseline, and in some cases significantly outperform the baseline. Secondly, while Nembhard and Osothsilp suggest that basing worker selection and assignment on L/F characteristics can provide the opportunity for improvement, we further demonstrate that several straightforward policies, which do not require instance specific optimisation, can also provide such opportunities.…”
Section: Discussionmentioning
confidence: 75%
“…We begin with a pool of n workers based on empirical data from the literature (Shafer, Nembhard, and Uzumeri 2001;Nembhard and Osothsilp 2005). The data span a 6-month period from the final inspection stations of a car radio assembly process.…”
Section: Worker Selection Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…As suggested in (2), the exponential L/F model has one weakness that it does count the cumulative number of periods for learning and forget- [7] or the hyperbolic recency L/F model [13,18,16].…”
Section: Exponential Learning and Forgetting Modelmentioning
confidence: 99%
“…Reviews of the literature on learning curves can be found in Dar-El (2000), Jaber and Sikström (2004), Jaber (2006), and Anzanello and Fogliatto (2011). Because of the availability of distributions from which to generate workforces, in this research, we use the hyperbolic learning model described in Nembhard and Osothsilp (2005). We note that, while we employ the hyperbolic learning model, most learning curves have simi-lar shapes and would support conclusions similar to those discussed in Section 4.4.…”
Section: Models Of Learningmentioning
confidence: 73%